Development Pattern of IT-Based Islamic Religious Learning After Covid-19 Pandemic in Coastal Serang Regency - Kharisul Wathoni; Irfan Anshori; Rumbang Sirojudin; Yuttana Kuakul; Wasehudin; Miftachul Huda (Jurnal Pendidikan Agama Islam, 2023)
Purpose - This study aims to determine the learning rate of Islamic religious education in the new-normal era after the COVID-19 pandemic in the coastal areas of Serang Regency. The constantly growing use of information technology has made most students reluctant to go to school. Design/methods/approach – This study is qualitative research. This research approach is descriptive. The data collection techniques used were observation, interview, and documentation. The number of informants in this study included students, teachers, and the community as parents of students. The respondent selection technique used purposive sampling, where the number of informants was 90% of the total sample. Findings - The findings in this study have included the use of a home visit strategy for post-pandemic learning continuity, where most students were reluctant to go to school and many students were contaminated with online games. The home visit method is a real form of visiting students one by one to provide understanding to parents and students about online learning, as well as a form of direct monitoring of the student learning process. Research implications/limitations – This research highlights how the educational process of the new normal era after the COVID-19 pandemic was in the coastal area of Serang Regency. Supposedly, the coastal area is a geographical location far from urban conditions, making the infrastructure aspect still very limited. Originality/value - This study presents the serious impact that occurred in the coastal area of Serang Regency when the learning process took place after the COVID-19 pandemic. Ranging from the personal pick-up strategy to numerous students who were reluctant to go to school to many students who were contaminated by online games.